Challenges to Promoting Resilience in Supply Chains Observed during the COVID-19 Pandemic: An Exploratory Study of the Amazon Region Using the TOPSIS Technique - Dhiordan Cunha Tadaiesky; Joaquim Lima das Neves Neto; André Cristiano Silva Melo; Rosley Anholon; Eliane de Castro Coutinho; Vitor William Batista Martins (Logistics, 2022)
Background: The COVID-19 pandemic has moved the world in every way, directly impacting supply chains globally and bringing major challenges to management, decision-makers, and companies of all sizes and sectors. This intensifies when it comes to the Brazilian Amazon region, a place that historically already lives with several maintenance projects focused on supply chain management (SCM). Methods: Thus, this research aimed to understand the main challenges faced by professionals in the supply chain area in the Amazon region through the development of a survey with professionals in the area. This study conducted a structured questionnaire containing 10 challenges related to SCM during the pandemic period to generate a ranking of these challenges using data analysis using means and comparative ordering using the TOPSIS Multicriteria Technique. Results: It was observed that the most relevant challenges for companies in this region were, respectively, distribution, economic problems, and interruptions in supply and demand. These obstacles promote debates with the literature and foster the expansion of knowledge about the insertion of resilience elements in supply chains in the Amazon. Conclusions: From a theoretical point of view and because it is exploratory research, the results serve as a basis for researchers in the area who aim to understand and expand the debates on this topic through future research. From a practical point of view, the results can help supply chain managers in the Amazon region who work directly in its maintenance and aim to maintain its resilience, since they already have the main challenges for the proper functioning of supply chains identified and ranked. Because it is an exploratory study, the results achieved can contribute significantly to the expansion of debates in the area and in a practical way with managers involved in activities that compose supply chains.